Peran Pemerintah Desa dan Peran Kelembagaan dalam Keberlanjutan Layanan Air Minum di Desa Sangketan Kecamatan Penebel Kabupaten Tabanan - I Gusti Ayu Lia Yasmita (Syntax Literate, 2023)
Water is a basic need that must be met by all living things on earth, the sustainability of drinking water services is a concern that must be resolved properly. Improving service development requires collaboration between the village government and the role of institutions in an effort to improve the standard of living of the community, especially in the field of clean water. This study used a descriptive qualitative method in which research was produced by describing written and oral sentences from sources using in-depth interviews. The results of this study are the role of the village government in assistance and supervision which is quite good, where the Sangketan village government includes drinking water into the BUMDesa unit so that it can easily carry out supervision and guidance. Supervision is carried out by reporting all management activities that are administrative and technical in nature. The guidance is carried out by bringing in people who have competence to be able to improve the competence of managing human resources. The guidance that is carried out is adjusted to the problems faced by managers in the field both in terms of management facilities and infrastructure up to the annual report which will later be carried out at village meetings by inviting village administration and community users.